521 Prevalence and Impact of Restless Legs in Patients with Myasthenia Gravis. (3rd May 2021) - AlGaeed, Mohanad; McPherson, Tarrant; Lee, Ikjae; Feese, Michelle; Aban, Inmaculada; Cutter, Gary; Kaminski, Henry; Karroum, Elias
Abstract: Introduction: Restless legs syndrome (RLS) is a sensori-motor disorder characterized by an urge to move the limbs during inactivity alleviated at least partially by walking/stretching. By contrast, myasthenia gravis (MG) is a neuromuscular disease with fluctuating weakness aggravated by continued muscle activity. Only a few studies addressed the prevalence of RLS in MG patients with limitations related to small sample size and/or usage of non-validated RLS screening tools. The aim of this study was to revisit the prevalence and impact of RLS in a large sample of MG patients using the validated 13-item short-form Cambridge-Hopkins diagnostic questionnaire for RLS (CH-RLSq13). Methods: The MG foundation of America patient registry was used to survey MG patients. Only patients aged ≥18 years, residing in the USA, and who answered "yes" to the question "Has your doctor diagnosed you with MG?" were included in this study. A survey including the CH-RLSq13, demographic information, disease related history, and patient reported outcomes including the MG15-item Quality of Life (MG-QOL15) and the MG-Activities of Daily Living (MG-ADL) instruments was sent to MG registry participants as part of the semi-annual follow up. Results: A total of 630 MG patients (age: 62.8±13.2; 54.9% Women; 94.6% White) completed the survey and met eligibility criteria (22% of patients receiving the survey). The prevalence of RLS was 14.8% (93/630). Clinically significant RLS (moderately/extremely distressing RLS ≥2–3 days/week) was present in 53 (8.4%) MG patients. MG patients with (versus without) RLS were significantly younger (p=0.0061), more women (p=0.0440), with higher (worse) depression (p<0.0001), MG-ADL (p=0.0001), and MG-QOL15 (p<0.0001) scores. Conclusion: Clinically significant RLS is prevalent in MG patients and is associated with a negative impact on mood, daily activities, and quality of life. Therefore, from a clinical practice it seems warranted to screen for RLS in MG patients. Support (if any): This study was not funded.